Assessment Of Coconut Flesh Waste And Its Solid Biochar For Briquette Production - Mohamed Noor, Nurhidayah (2022)
The main objective of this study is to investigate the potential of coconut flesh waste (CFW) biochar from pyrolysis for solid biofuel (briquette) production. The CFW biochar was produced via mild pyrolysis from 200°C to 300°C and slow pyrolysis from 350°C to 600°C.